A Low-Cost Real-Time BCI Integration for Automated Door Opening System - Guner, Mustafa; Erkmen, Burcu (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
Based on the ElectroEncephaloGraphy (EEG) signals obtained by noninvasive methods, Brain-Computer Interface (BCI) technologies provide real-time communication of individuals within the cyber-physical systems. However, this research area still needs low-cost solutions to become a research topic widely all around the world. In this paper, a low cost and productive BCI equipment was developed to assist daily living activities for disabled people. The control application of an integrated approach aims to open and close a door equipped with an EEG-based lock system using eye blink signals is developed. The proposed easy-to-use, portable BCI system includes cost-effective hardware/software components, modular and flexible configuration features and Bluetooth-enabled real-time data processing units. The developed BCI hardware is based on Texas Instruments ADS1299 AFE ADC, which features high flexibly in configuring of measure of various biopotentials from the human body using designed active/passive dry electrodes. Besides it is equipped with a built-in real-time data storage unit and accelerometer to make an online diagnosis, and data fusion at the interested signal investigation. Furthermore, desktop software has been implemented in the QT SDK environment, which can integrate remote BCI hardware during configuration. Experimental results of the designed system were compared with the results of the commercial-grade counterpart.
Keywords: Brain-computer interface; cyber-physical system; Door Lock Accessing System; ElectroEncephaloGraphy; BRAIN-COMPUTER INTERFACES; Computer Science; Engineering